Reflexões sobre Interação e Colaboração a partir de um Curso Online - Dantas, Sérgio Carrazedo [UNESP]; Lins, Romulo Campos [UNESP] (FapUNIFESP (SciELO), 2017)
The central concern of this study was to investigate interaction and collaboration processes in an online community of mathematics teachers. Considering the Model of Semantic Fields as our theoretical and methodological foundation, we tried to give visibility to the characteristics and dynamics of interaction. In order to do so, we have developed a technological structure that made it possible for teachers involved in an extension course, to talk to their peers, and through their decision-making, establish their collaborative networks. We reached a clear characteristic of the self-management feature of the organizational processes of an online community that we created, and that which we called the collaborative interaction.
Reflections on interaction and collaboration of an online course
Keywords: Collaboration; Collaborative interaction; Continued education for mathematics teachers; Interaction